Aktualisasi Nilai- Nilai Sakral Pancasila dalam Budaya Reba - Maria Theresia Avila Nia; Yasinta Advensia Wea; Maria Godaliva Mamo Keu; Hildegardis Ule; Fontinia Bebe Taung; Vantriana Ida Bewa (Universitas Maritim AMNI Semarang, 2025)
Reba Bajawa culture, an annual traditional ritual in East Nusa Tenggara, is a tangible manifestation of the noble values of Pancasila, the Indonesian state philosophy. Through three main stages—Kobe Dheke, Kobe Dhoi, and Kobe Sui—this ritual integrates spiritual, social, and ecological aspects. The values of divinity, humanity, unity, democracy, and social justice are reflected in each stage of the ritual, from offerings to ancestors to mutual cooperation in building piles of yams. The Reba Bajawa ritual is not just a traditional ceremony but also a culturally rich heritage. This research examines how Pancasila values are implemented in each stage of the Reba ritual. The results show that the Reba ritual is an effective means of preserving the nation's noble values, strengthening cultural identity, and building a harmonious society. Through a deep understanding of the Reba ritual, it is hoped that it can raise public awareness of the importance of preserving the nation's culture. In the era of globalization, traditional values are often marginalized. However, the Reba Bajawa ritual proves that noble values such as mutual cooperation, tolerance, and respect for nature are still relevant today. This study analyzes how the Pancasila values contained in the Reba ritual can be an inspiration in building a better Indonesian society. This research aims to analyze how Pancasila values are embodied in the Reba cultural practice and its implications for national character education.